FAKTOR PENDORONG INFLASI TERHADAP PERTUMBUHAN PEREKONOMIAN INDONESIA - Juwita, Juwita; Resnawati, Resnawati; Safaringga, Afriyanti Helen; Anggraini, Fitri (Jurnal Pendidikan Ekonomi, 2024)
Inflation is an indicator of economic stability which is a major concern for developing countries. The rate of economic growth is the rate growth from one period to another expressed as a percentage. The economic growth ladder shows that income in a country changes or economic income is higher over a certain period that from crisis moneter then just like paralaks circle. This research is a library research or library research. Literature research serves as a tool to solve problems that are not yet clear, comprehensive, complex, dynamic and meaningful from literary sources. Data sources are things that must be obtained in research because research goes well with quality and appropriate data sources. Sources of information for this research are books and articles that are appropriate to the research subject.